Rehabilitation of Lignite Mine Spoils in the Indian Arid Zone-An Ecological Approach - Kumar, Suresh; Kumar, Praveen (Annals of Arid Zone, 2016)
Rehabilitation of barren lignite mined spoiled lands was carried out in the Barmer district of Indian arid zone following ecological approach. Being highly sodic in nature, the spoil surface was overlain with a layer of dune soil in varying thickness. The three treatments of thickness of topsoiling were 30, 45 and 60 cm. Landshaping of resultant surface with 5% slope was done to make micro catchment for water harvesting. Multipurpose species of trees, shrubs, creepers and grasses were selected. Woody perennial saplings were prepared for transplantation in 60×60×60 cm pits filled with a mixture of local soil and FYM in 2:1 ratio. Plantation was carried out in three seasons i.e., July, September and March. Results revealed that overall survival of species planted at lignite mine spoil was 85.28%. Maximum growth was observed in Parkinsonia aculeata followed by other species. Month of March has proved to be better plantation season than July and September in high sodium containing backfill. Micro catchments did not favour the growth of planted species. Thickness of 60 cm topsoiling emerged as most optimum for survival and growth of species. Monitoring of species growth and survival revealed that most suitable species for lignite mine spoil back fill in this area are Parkinsonia aculeata, Acacia nubica, Circidium floridum, Acacia tortilis, Salvadora oleoides, Dichrostachys nutans, Acacia senegal and Tecomella undulata in that order. Role of local people and NGO’s for participatory mine rehabilitation has been highlighted as a major future requirement of these programs.